Third COVID-19 vaccine dose for people with multiple sclerosis who did not seroconvert following two doses of BBIBP-CorV (Sinopharm) inactivated vaccine: A pilot study on safety and immunogenicity - Sedaghat, Nahad; Etemadifar, Masoud; Lotfi, Noushin; Sayahi, Farnaz; Chitsaz, Ahmad; Salari, Mehri; Ghasemi Movaghar, Alireza (Frontiers in Immunology, 2023)
Background: People with multiple sclerosis (pwMS) on anti-CD20 therapies (aCD20) and fingolimod have shown inadequate humoral responses to COVID-19 vaccines. Objective: To pilot larger studies by demonstrating the safety, and comparing the immunogenicity of different types of third doses in seronegative pwMS after two doses of BBIBP-CorV inactivated vaccine. Methods: In December 2021, subject to receiving their third dose, being COVID-19-naiive and receiving no corticosteroid within two months, we measured the level of anti-SARS-CoV-2-Spike IgG in pwMS seronegative after two shots of BBIBP-CorV inactivated vaccine. Results: We included 20/29 pwMS who received adenoviral vector (AV), 7/29 who received inactivated and 2/29 who received conjugated third doses. No serious adverse events were reported two weeks post-thid dose. The pwMS receiving AV third doses showed significantly increased IgG concentrations, while only the ones not on aCD20 and fingolimod responded to inactivated third doses. An ordinal logistic multivariable generalized linear model indicated that age (per year β: -0.10, P=0.04), type of disease-modifying therapy (aCD20 β: -8.36, P<0.01; fingolimod β: -8.63, P=0.01; others: reference), and type of the third dose (AV or conjugated β: 2.36, P=0.02; inactivated: reference) are predictive of third dose immunogenicity among pwMS who remain seronegative after two shots of BBIBP-CorV vaccine. Statistical significance was not achieved for variables sex, MS duration, EDSS, duration of DMT, duration of third dose to IgG test, and duration from last aCD20 infusion to third dose. Conclusion: This preliminary pilot study highlights the need for further research to determine the optimal COVID-19 third dose vaccination.